Orí, na tradição dos Orixás: um estudo nos rituais do Ilé Àsé Òpó Afonjá - Rodrigues, Maria das Graças de Santana (2009)
The research carries out his first approach to the archetypical unconscious present in the world of symbols. Symbols standing in the Ilé Àsé Òpó Afonjá religious context regarded as a living heap of African cultural tradition in Brazil, a historical and cultural heritage, a Nago traditional jewel box of learning in diasporic Bahia. Bahia, a privileged area for these cultures preservation, offers us the possibility to examine more deeply the African contribution to Brazilian identity constitution. We have present in our minds the African Diaspora, especially on the two ways route between Nigeria and Salvador in Bahia. The area in which has been built this cultural bridge was the South Atlantic. In this area a continuous cultural bridge has been built along the last three hundred years. Comparisons and connections have in traffic and cultural mobility two of his constitutive pillars. Our research is restricted to the Orí, to the comprehension of his nature and characteristics in human existence as psycho-social phenomenon. In the African cosmovision, strictly unitary, the visible world and the invisible one are not separated, they interpenetrate each other in continuity, so the importance to well understand the interrelation between them, between the Orun and the Aiyé. The Orí presence and motion in these worlds is marked by an important role. Our hypothesis understands that Orí fulfils an epistemological function in the Orishas tradition. Thus, the comprehension of his meaning is fundamental for the Orishas acquaintance as well as for their rituals. For that tradition descendents the undermost gestures do make sense. They are actions that wave to the human condition boundaries reflected in the rituals. This means that on the Terreiro and in the regarded rituals he is meant again. Therefore, his symbols can be read by the archetypal way. Orí inside the human being is a conscious light. He is the African ancestry meant again in the New Atlantic